Tahap literasi komputer pelajar sekolah menengah di Kedah - Normala Ismail; Zaliha Hj. Hussin; Mohammad Kamil Ariff Khalid (penerbit ukm, 2005)
Computer literacy has become the main agenda in today’s life. It has become one of the main sources for a country’s development. The main objective of the research is to measure the level of computer literacy among upper secondary school students in the state of Kedah. Moreover the research is to identify the relationship between parent’s level of education and income with student’s computer literacy. Furthermore the study also explores the relationship between student’s attitude and computer skill with computer literacy. Data was collected through the questionnaires distributed to 698 students from form four, form five and Lower Six in twelve secondary schools of seven provinces in Kedah state. Tools for measurement used in this study are Attitude Toward Computer Scale (ATCS), Computer Self – Efficiency Scale (CSES) and Minnesota Computer Literacy and Awareness Assessment Test (MCLAAT). To measure the objective and to examine the hypotheses of the study, tests such as mean, percentage, Chi Square and Cramer V are used. Significance level of 0.05 is used to accept or to reject the null hypothesis. Data is analyzed using Statistical Package for Social Sciences (SPSS) version 12.0. The study finds that the student’s computer literacy level is moderately high with mean score of 66.67%. The overall findings conclude that there is a significance relationship between parent’s level of education and income with student’s computer literacy. However there is no significance relationship between student’s attitude and computer skill with computer literacy. The study suggests that schools should offer more computer related activities as to increase student’s computer literacy level.